Distribution of Ponds and Its Change Detection in Tehsil, Ranchi District, Jharkhand State, India - Shams, Shefa; Patel, Dr. Nilanchal; Shukla, Dr. Sudhakar (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 10 No 1&2 (2023): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2023)
Ponds serve multiple purposes in the biosphere and are an essential element of the hydrological system. However, due to the ponds tiny dimensions, the study of their natural environments is frequently disregarded. Despite a doubt, many significant responsibilities in our life are carried out by small activities. Ponds offer environmentally friendly responses to a few of the most significant issues associated with managing water and climate change. Distributing ponds delivers a more equitable distribution of a region's water resources. By strategically placing ponds across several blocks, it becomes simpler to provide water necessities for diverse populations, especially throughout regions where water shortages are now an important issues. Digitizing ponds of 2013 and 2022 using Google Earth and overlaid the ponds over Tehsil, Ranchi District and calculate the change detection of Ponds.